2021
DOI: 10.18060/25331
|View full text |Cite
|
Sign up to set email alerts
|

All That You Can’t Leave Behind - Essential Post-COVID Technology and Pedagogy

Abstract: The COVID-19 pandemic forced many institutions to adapt quickly and substitute technology-based online or remote instruction in place of in-person instruction. This adaptation caused many faculty to develop new technology fluencies, which can provide more flexibility and innovation moving forward. However, the technological lessons learned from the COVID-19 pandemic are somewhat conflicting, as we have also learned that there are places where in-person instruction is extremely valuable. As we move beyond COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…While some have suggested that online service learning opportunities, in general, may be more or equally effective compared to face-to-face experiences (McGorry, 2012;Waldner, 2015), the current article only addresses the need to plan for alternatives for mutually beneficial community engagement when face-to-face engagement is limited or impossible. Moving into the future, as faculty and community partners are committed to providing high-quality experiential learning opportunities, they have more opportunities to collaborate to identify and address current needs and interests to decide if face-to-face, virtual, or a combination of each best suits their programs and courses (Schaus et al, 2022), and to develop robust contingency plans in case of a disruption to operations. Such contingency planning may allow the continuation of community-engaged learning opportunities in times of crisis.…”
Section: Community Engagement In the Futurementioning
confidence: 99%
“…While some have suggested that online service learning opportunities, in general, may be more or equally effective compared to face-to-face experiences (McGorry, 2012;Waldner, 2015), the current article only addresses the need to plan for alternatives for mutually beneficial community engagement when face-to-face engagement is limited or impossible. Moving into the future, as faculty and community partners are committed to providing high-quality experiential learning opportunities, they have more opportunities to collaborate to identify and address current needs and interests to decide if face-to-face, virtual, or a combination of each best suits their programs and courses (Schaus et al, 2022), and to develop robust contingency plans in case of a disruption to operations. Such contingency planning may allow the continuation of community-engaged learning opportunities in times of crisis.…”
Section: Community Engagement In the Futurementioning
confidence: 99%